Imizwa evezwa wukuqanjwa kwemizi yakwandima eskhaleni sebomvu, Enkandla - Ndima, Londokuhle Nqobani Blessing (My University, 2021)
This research investigates the sentiments expressed after the naming of Ndima homestead names in eSkhaleni Sebomvu, Nkandla. The researcher believes in the view that in modern times the naming of homesteads has been neglected because of the impact of modern life and the impact of democratic government. It is disheartening to see indigenous peoples abandon their values, cultures, languages and all that distinguishes them from others, as it disturbs its history and tradition. The research used a data collection approach that understands the reality of people in different communities, a qualitative approach was used to gather information and feedback from participants about homestead naming. Hermeneutics theory and the Socio-Onomastics theory were employed to search for and analyze various ideas contained by the homestead names. The research findings were divided into different themes and into contexts of the ancestral wives who are responsible for the homesteads researched. These themes also reveal the relationship of the homesteads and their naming. The research also represented the argument on the homesteads named after variety of events that name givers experienced in their own lives, to people around them and in the community at large
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2021